Non-marital fertility in South Africa: trends, determinants and implications - Kara, Reesha (Rhodes University, Faculty of Humanities, Department of Sociology, 2020)
Background: Non-martial fertility is traditionally associated with teenage pregnancy however international and South African literature has detailed increases in the number of adult women who are having children outside of a marriage. South African literature on non-marital fertility is sparse as it lacks a national overview of the trends and determinants of non-marital fertility among women aged 30 and older. The aim of this study was to present a national overview of non-marital fertility among women aged 30 and older. South African's attitudes to and opinions of non-marital fertility were also investigated, and the lived realities of older mothers were explored. Methods: A mixed-methods research design was employed where the General Household Survey, National Income Dynamics Study and the South African Social Attitudes Survey were the main data sources. Using these data sets, descriptive and inferential statistics were computed using Stata. Using purposive and snowball sampling, four never-married older mothers (NMOMs) from KwaZulu-Natal (Durban) were identified as research participants. The in-depth life histories of these women were collected through face-to- face semi-structured interviews. Results: The results show an 18.43% increase in never-married mothers aged 15- 49 between 2002 and 2017 and interestingly, this increase is not necessarily driven by older mothers (30-49). NMOMs belonged to households with a lower average per capita total monthly household income (R1873.91) compared to all mothers aged 30-49 (R3428.76). NMOMs were also more likely to live in female-headed households (89.52%), to be household heads (64.22%) and to live in traditional areas (35.72%). Between 2002 and 2017, there was a 76.76% increase in mothers (aged 30-49) who were never married and a 7.74% decrease in those who were married, indicating a change in the marital profile of mothers. Despite this national increase in non-marital fertility, South African's believe that premarital sexual activity is wrong, and that childbearing should take place within a marriage. Similar sentiments were echoed in the in-depth life histories as being the sole breadwinner and primary caregiver, the research participants experienced challenges as single mothers. Conclusion and recommendations: The study has found that there has been an increase in non-marital fertility in South Africa between 2002 and 2017 and that there is an economic element to non-marital fertility in the country. Additional research into non-marital fertility at a national level is recommended with a focus on all women aged 15-49.
Keywords: Fertility, Human -- South Africa; Child rearing -- South Africa; Parenting -- South Africa; Motherhood -- South Africa